To determine whether the function \( f(x) = -x^5 - 6x^3 \) is odd, even, or neither, we will use the definitions of odd and even functions:
- Even Function: A function is even if \( f(-x) = f(x) \) for all \( x \).
- Odd Function: A function is odd if \( f(-x) = -f(x) \) for all \( x \).
Let's check the values of the function provided for \( f(-x) \):
-
Calculate \( f(-2) \): \[ f(-2) = -(-2)^5 - 6(-2)^3 = -(-32) - 6(-8) = 32 + 48 = 80 \]
-
Calculate \( f(-1) \): \[ f(-1) = -(-1)^5 - 6(-1)^3 = -(-1) - 6(-1) = 1 + 6 = 7 \]
-
Calculate \( f(0) \): \[ f(0) = -0^5 - 6(0)^3 = 0 \]
-
Calculate \( f(1) \): \[ f(1) = -(1)^5 - 6(1)^3 = -1 - 6 = -7 \]
-
Calculate \( f(2) \): \[ f(2) = -(2)^5 - 6(2)^3 = -32 - 48 = -80 \]
Now, we compare \( f(-x) \) with \( -f(x) \):
- For \( x = 2 \): \[ f(-2) = 80 \quad \text{and} \quad -f(2) = -(-80) = 80 \]
- For \( x = 1 \): \[ f(-1) = 7 \quad \text{and} \quad -f(1) = -(-7) = 7 \]
- For \( x = 0 \): \[ f(0) = 0 \quad \text{and} \quad -f(0) = -0 = 0 \]
Since for all values checked \( f(-x) = -f(x) \), the function \( f(x) = -x^5 - 6x^3 \) is confirmed to be an odd function.
Thus, the correct response is: odd